A fixed inhaled nitrous oxide/oxygen mixture as an analgesic for adult cancer patients with breakthrough pain: study protocol for a randomized controlled trial. Issue 1 (December 2017) - Liu, Qiang; Wang, Yu; Luo, Xiang-Jiang; Wang, Ning-Ju; Chen, Ping; Jin, Xin; Mu, Guo-Xia; Chai, Xiao-Min; Zhang, Yue-Juan; Li, Yu-Xiang; Yu, Jian-Qiang
Abstract Background The management of breakthrough pain in cancer patients is always a challenge for medical professions. Occurring in 80% of cancer patients with advanced disease, breakthrough pain significantly decreases both patient's and caregiver's quality of life. The aim of this study is to assess the analgesic efficacy of a fixed inhaled nitrous oxide/oxygen mixture for adult cancer patients with breakthrough pain. Methods/design This is a randomized, placebo-controlled, double-blind study; it will be conducted in the General Hospital of Ningxia Medical University. The target study subjects are at least 18 years old, and are hospitalized cancer patients who are receiving routine opioids to control cancer-related pain but still experience breakthrough pain. A total of 240 patients will be recruited and randomly allocated between three treatment groups (A, B, C) and a control group (group D) in a ratio of 3:1. All treatment groups (A, B, C) will receive standard pain treatment (oral immediate-release morphine) plus a pre-prepared nitrous oxide/oxygen mixture, and the control group (D) will receive the standard pain treatment plus oxygen. Patients, doctors, nurses, and data collectors are all blind to the experiment. Assessments will be taken before treatment (T0), at 5 min (T1) and 15 min (T2) during treatment, and at 5 min after treatment (T3). The primary endpoint measures will be the percentage of patients whose pain is relieved at T1, T2, and T3. Secondary outcome measures will include the safety of treatment, adverse events, and satisfaction from both health professionals and patients. Discussion This study aims to provide an effective and practical intervention for a fast breakthrough pain relief and to improve cancer patients' quality of life significantly. The Evidence-Based Medicine Working Group claim that a randomized, double-blind, placebo-controlled experimental intervention is the most appropriate design to demonstrate its efficacy, so this study could give a new approach to controlling breakthrough pain episodes. Trial registration ChiCTR-INC-16008075 . Registered on 8 March 2016.